The Impacts of Outdoor Learning Activities on Children’s Self Development - Sari, Aidha Nur Indah (Universitas Swadaya Gunung Jati, 2016)
This research concentrates on investigating the impacts of outdoor learning activities in the nature based Kindergarten School of Universe Al-Ghiffari Cirebon. The research is attempted to find out whether outdoor learning activities impact children‟s selfdevelopment or not. By doing triangulation as the method of this research, it will help to get the results more efficient, stronger, and credible. The results found that outdoor learning activities impact positively and effectively on children‟s progress across all areas of children‟s self developments. These areas include cognitive development, affective development, personal, social, and emotional development, and physical and behavioral development.